Peningkatan Keterampilan Menulis Puisi Melalui Teknik Akrostik Berbantuan Media Canva pada Peserta Didik Kelas X2 SMA N 2 Semarang - Nevia Indah Winaryuni; Ahmad Rifai; Erni Hidayati (Jurnal Pendidikan Guru Profesional, 2024)
This research aims to determine students' abilities in writing poetry using the acrostic technique. This is important to teach in improving poetry writing skills. The procedure carried out in this research was to apply the classroom action research method using descriptive analysis. The purpose of this analysis is to determine the average value and also calculate the percentage of learning outcomes, and quantitative analysis is carried out to evaluate the value of learning outcomes. The learning process uses acrostic techniques, the main focus of which is to strengthen students' understanding of analysis, used to explore psychological aspects. This research involved 36 students. In this context, teachers develop learning for Indonesian language subjects, especially in writing poetry, by applying acrostic techniques. Based on the research results, there are several improvements in learning to write poetry using the acrostic technique assisted by Canva media. This improvement means that students are more critical in analyzing keywords found in writing poetry so that students can easily choose appropriate diction followed by arranging words to form poetry lines. This research method uses a qualitative and quantitative approach. Data analysis techniques describe and conclude data based on observation results. The results of this research showed an increase in poetry writing skills through the acrostic technique assisted by Canva media, namely that the average score of students in cycle I was 84.5 and in cycle II there was an increase of 87.6. Meanwhile, the highest score in cycle I was 90 and cycle II was 96. The percentage of completion level in cycle I was 94.44% and cycle II was 97.22%. So there is good improvement in writing poetry using assisted acrostic techniques media canva.